Determinants of maternal mortality in Eastern Mediterranean region: A panel data analysis - Bayati, Mohsen (Med J Islam Repub Iran, 2016)
Background: As one of the main criteria of health outcomes, maternal mortality indicates the socioeconomic development level of countries. The present study aimed at identifying and analyzing the effective factors on maternal mortality in Eastern Mediterranean Region (EMR) of the World Health Organization (WHO). Methods: Analytical model was developed based on the literature review. Panel data of 2004-2011 periods for 22 EMR countries was used. Required data were collected from WHO online database. Based on results of diagnostic tests for panel data model, parameters of model were estimated by fixed effects method. Results: Descriptive statistics demonstrated the large disparities in social, economic, and health indicators among EMRO countries. Findings obtained from evaluating the model showed a negative, significant relationship between GDP per capita (β=-0.869, p<0.01), health expenditure) β=-0.525, p<0.01 (female literacy rate) β=-1.045, <0.01 (skilled birth attendance) β=-0.899, p<0.05) and maternal mortality rate. Conclusion: Improved income and economic development, increased resources allocated to the health sector, improved delivery services particularly the increased use of trained staff in the delivery, improve quality of primary care centers, mitigating the risks of marginalization and its dangers, and especially improving the level of women's education and knowledge are the key factors in policy making related to maternal health promotion.